KUS-ALJABAR DAN ASPEK ALJABAR TERKAIT - Melly Nur Aziz; Suryoto Suryoto (Jurnal Matematika, 2014)
A KUS-algebra is a nonempty set with a binary operation and has special element and satisfy the axioms of KUS-algebra. KUS-algebra structure has simialarities with other algebraic structures that KU-algebra. Every KUS-algebra on  where  then  is not a KU-algebra. That the other algebraic structures, KUS-algebra also has  substructure called KUS-subalgebra, ideal of KUS-algebra called KUS-ideal and homomorphism of KUS-algebra called KUS-homomorphism.